Analysis of Regional Government Expenditures of Central Bangka Regency - Ratih Kusumastuti; Septi Anggraeni (Equity: Jurnal Ekonomi, 2023)
Analysis of Regional Government Expenditures in Central Bangka Regency. This study aims to analyze spending in terms of spending growth, spending compatibility and the ratio of spending to PDRB in Central Bangka Regency in 2018-2022. This study uses secondary data in the form of Budget Realization Reports (LRA) of the Central Bangka Regency regional government and Central Bangka Regency economic statistics sourced from the Central Bureau of Statistics (BPS) of Central Bangka Regency. The data analysis technique is in the form of quantitative analysis, namely by using the formula for growth and spending ratios. The results of the analysis show that the realization of regional government spending in Central Bangka Regency in 2018-2022 has fluctuated with an average growth of 17.85% per year, this is not in line with the growth in realized revenues which tends to decrease each year. The ratio of operational expenditure to total expenditure tends to increase with an average of 70.85% per year and this ratio dominates the total regional expenditure expenditure while the ratio of capital expenditure to total expenditure tends to decrease with an average of 15.31% per year . The ratio of regional spending to PDRB for the regional government of Central Bangka Regency in 2018-2022 tends to decrease with an average ratio of 15.01% per year. The value of this ratio is also influenced by the growth value of PDRB and total spending. The growth of total regional government spending in Central Bangka Regency is relatively smaller when compared to the PDRB growth.